Perfil de fenólicos e propriedades bioativas de méis de abelhas sem ferrão (Melipona semingra merrille) do Estado do Amazonas. - Silva, Isnandia Andrea Almeida da (2013)
Melipona semingra merrillae is a honey producing stingless bee species, whose honey properties are native to the Amazon Region, honey, honey whose properties are still poorly known. In the present study honey samples produced by Melipona seminigra merrillae in seven counties from Amazonas state Brazil, namely: Boca do Acre (BAJ), Pauni (PAU), Manaus (MAO), Rio Preto da Eva (RP), Lábrea (LAB), Maués (ME) and Coari (CO) were investigated. The study was performed studying the physic-chemical characteristics (pH, acidity, ash, proteins, hydroxymethylfurfural, and reducing sugars), thermal degradation profile, antioxidant activity, antimicrobial activity and profile of phenolic compounds. In the study of the antioxidant properties were prepared methanol extracts and ethyl acetate fractions of the honeys, in which samples were performed tests for the evaluation of the antioxidant activity (DPPH, ABTS, HO, β-carotene/linoleic acid system and FRAP). The data of the melissopalynological analysis characterized four of the seven honeys and monoflorals. In relation to the physic-chemical analyses, most of the parameters analyzed showed average values adequate for the human consumption, with the exception of moisture and reducing sugars. The thermogravimetric data showed that all the honey samples displayed a similar thermal degradation profile. As for the antimicrobial activities, the ethyl acetate fractions of the samples LAB, ME and CO presented the best results with minimal inhibitory concentration (MIC) varying from 256 to 512 μg.mL-1. The promising results of antioxidant activity found in honey, extracts and fractions can be explained by the presence of phenolic compounds: gallic acid, 3,4-dihydroxybenzoic acid, 4-hydroxybenzoic acid, trans-trans abscisic acid, cis-trans abscisic acid, vanillic acid, syringic acid, coumaric acid, cinnamic acid and the flavonoids taxifolin, naringenin, luteolin and catechol, whose presence in Brazilian honeys is reported for the first time. Taxifolin was identified in all the samples, in contents ranging from 3.87 to 67.2 mg/100g of honey, suggesting that it is a phenolic indicator for the honeys produced by the species. The total phenolic contents were expressive for the evaluated samples, what could support the consumption of these honeys as a functional food.